Eye of the storm : the impact of climate shocks on inflation and growth - Cevik, Serhan (2023)
What is the impact of climate change on inflation and growth dynamics? This is not a simple question to answer as climate shocks tend to be ubiquitous, but with opposing effects simultaneously on demand and supply. The extent of which climate-related shocks affect inflation and economic growth also depends on long-run scarring in the economy and the country’s fiscal and institutional capacity to support recovery. In this paper, we use the local projection method to empirically investigate how climate shocks, as measured by climate-induced natural disasters, influence inflation and economic growth in a large panel of countries over the period 1970–2020. The results shows that both inflation and real GDP growth respond significantly but also differently in terms of direction and magnitude to different types of disasters caused by climate change. We split the full sample of countries into income groups—advanced economies and developing countries—and find a striking contrast in the impact of climate shocks on inflation and growth according to income level, state of the economy, and fiscal space when the shock hits.